Hydrogen as an Energy Carrier—An Overview over Technology, Status, and Challenges in Germany - Caroline Willich (J)
Hydrogen is set to become an important energy carrier in Germany in the next decades in the country’s quest to reach the target of climate neutrality by 2045. To meet Germany’s potential green hydrogen demand of up to 587 to 1143 TWh by 2045, electrolyser capacities between 7 and 71 GW by 2030 and between 137 to 275 GW by 2050 are required. Presently, the capacities for electrolysis are small (around 153 MW), and even with an increase in electrolysis capacity of >1 GW per year, Germany will still need to import large quantities of hydrogen to meet its future demand. This work examines the expected green hydrogen demand in different sectors, describes the available technologies, and highlights the current situation and challenges that need to be addressed in the next years to reach Germany’s climate goals, with regard to scaling up production, infrastructure development, and transport as well as developing the demand for green hydrogen.